LEVERAGING GOOGLE CLASSROOM FOR ELT: A SYSTEMATIC REVIEW - Mika Avialisha Tama; Amalia Zulfan Hadi; Nafan Tarihoran (INTERNATIONAL JOURNAL OF SOCIETY REVIEWS, 2025)
The integration of computerized stages in English Dialect Instructing (ELT) has revolutionized conventional learning by improving openness, collaboration, and engagement. Among these stages, Google Classroom has ended up a broadly utilized device for overseeing coursework, giving organized composing hone, and cultivating talks intelligently. This think-about points to methodically surveying existing inquiries about the benefits, challenges, and general adequacy of Google Classroom in ELT by distinguishing which English dialect aptitudes are most moved forward and analyzing which instructive levels advantage the foremost. Employing a precise survey strategy, this consider analyzes peer-reviewed diary articles, conference papers, and theses distributed between 2019 and 2024. The discoveries demonstrate that Google Classroom is especially compelling in upgrading composing and perusing comprehension abilities, particularly at the college level, where understudies have higher computerized proficiency. In any case, talking and tuning in abilities stay immature due to the platform's nonconcurrent nature. Furthermore, challenges such as mechanical boundaries, educator preparing crevices, and adjustment troubles affect its viability. Future investigations ought to center on cross-breed learning models and progressed educational procedures to maximize the potential of Google Classroom in ELT, guaranteeing a more comprehensive and intuitive dialect learning involvement.